Surveillance for Wilms tumour in at-risk children: pragmatic recommendations for best practice. Issue 12 (20th July 2006) - Scott, R H; Walker, L; Olsen, Ø E; Levitt, G; Kenney, I; Maher, E; Owens, C M; Pritchard-Jones, K; Craft, A; Rahman, N
Abstract : Background: Most Wilms tumours occur in otherwise healthy children, but a small proportion occur in children with genetic syndromes associated with increased risks of Wilms tumour. Surveillance for Wilms tumour has become widespread, despite a lack of clarity about which children are at increased risk of these tumours and limited evidence of the efficacy of screening or guidance as to how screening should be implemented. Methods: The available literature was reviewed. Results: The potential risks and benefits of Wilms tumour surveillance are finely balanced and there is no clear evidence that screening reduces mortality or morbidity. Prospective evidence-based data on the efficacy of Wilms tumour screening would be difficult and costly to generate and are unlikely to become available in the foreseeable future. Conclusions: The following pragmatic recommendations have been formulated for Wilms tumour surveillance in children at risk, based on our review: (1) Surveillance should be offered to children at >5% risk of Wilms tumour. (2) Surveillance should only be offered after review by a clinical geneticist. (3) Surveillance should be carried out by renal ultrasonography every 3–4 months. (4) Surveillance should continue until 5 years of age in all conditions except Beckwith–Wiedemann syndrome, Simpson–Golabi–Behmel syndrome and some familial Wilms tumour pedigrees where it should continue until 7 years. (5) Surveillance can be undertaken at a local centre, but should be carried out by someone with experience in paediatric ultrasonography. (6) Screen-detected lesions should be managed at a specialist centre.